If you bite & devour one another Biblical principles for handling conflict - Strauch, Alexander (Littleton, Colo. Lewis and Roth Publishers, 2011)
"Conflict in churches is a pervasive problem we know all too well. If You Bite & Devour One Another is the only book of its kind, examining all the biblical passages on conflict and outlining key scriptural principles for handling various kinds of confl
Keywords: Church controversies. Conflict management -- Religious aspects -- Christianity